Spirituality Works as A Mediator Between Authentic Leadership and Teacher Performance in The Digital Era - Aminah, Lailatul; Abidin, Munirul (Abjadia : International Journal of Education, 2025)
Teacher performance is an important element in the success of education. The higher the teacher's performance, the greater the chance of educational success that can be achieved. In this case, the role of authentic leadership is crucial. Authentic leadership is important in building a work climate that supports the spiritual values and professionalism of teachers. This study aims to analyze the impact of authentic leadership and work spirituality on teacher performance. In addition, this study explores whether work spirituality mediates the relationship between authentic leadership and teacher performance in the digital age. The approach used in this study is a quantitative approach by collecting data through questionnaires in google form which is distributed through social media platforms in the form of WhatsApp and analyzed using the SmartPLS 4 program. This research was conducted in all Madrasah Ibtidaiyah in Licin District with 52 respondents from all populations. The findings show that authentic leadership has a positive and significant effect on teacher performance, both directly and through the mediation of work spirituality. The direct influence of authentic leadership on teacher performance was 0.367 (P value = 0.014 0.05), while the direct influence of work spirituality on teacher performance was 0.606 (P value = 0.000 0.05). In addition, the spirituality of work mediating the relationship between authentic leadership and teacher performance was 0.388 (P value = 0.000 0.05). These findings reinforce the theory that authentic leadership can improve teacher performance through strengthening work spirituality. This research emphasizes the importance of the values of honesty, work meaning, and integrity in the context of education in the digital era.